Chemical, experimental, and morphological evidence for diagenetically altered melanin in exceptionally preserved fossils - Colleary, Caitlin (Proc Natl Acad Sci U S A, 2015)
In living organisms, color patterns, behavior, and ecology are closely linked. Thus, detection of fossil pigments may permit inferences about important aspects of ancient animal ecology and evolution. Melanin-bearing melanosomes were suggested to preserve as organic residues in exceptionally preserved fossils, retaining distinct morphology that is associated with aspects of original color patterns. Nevertheless, these oblong and spherical structures have also been identified as fossilized bacteria. To date, chemical studies have not directly considered the effects of diagenesis on melanin preservation, and how this may influence its identification. Here we use time-of-flight secondary ion mass spectrometry to identify and chemically characterize melanin in a diverse sample of previously unstudied extant and fossil taxa, including fossils with notably different diagenetic histories and geologic ages. We document signatures consistent with melanin preservation in fossils ranging from feathers, to mammals, to amphibians. Using principal component analyses, we characterize putative mixtures of eumelanin and phaeomelanin in both fossil and extant samples. Surprisingly, both extant and fossil amphibians generally exhibit melanosomes with a mixed eumelanin/phaeomelanin composition rather than pure eumelanin, as assumed previously. We argue that experimental maturation of modern melanin samples replicates diagenetic chemical alteration of melanin observed in fossils. This refutes the hypothesis that such fossil microbodies could be bacteria, and demonstrates that melanin is widely responsible for the organic soft tissue outlines in vertebrates found at exceptional fossil localities, thus allowing for the reconstruction of certain aspects of original pigment patterns.